2019
DOI: 10.1001/jamapediatrics.2019.0458
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sexual Initiation Before Age 13 Years Among Male Adolescents and Young Adults in the United States

Abstract: Key Points Question Does the prevalence of sexual initiation before age 13 years among males in the United States vary by race/ethnicity, location, and socioeconomic status? Findings This cross-sectional study of 19 916 male high school students and 7739 males aged 15 to 24 years found substantial variation in the rates of sexual onset before 13 years of age across metropolitan areas and by race/ethnicity, with rates as high as 28% among non-Hispanic black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 46 publications
(93 reference statements)
3
40
1
Order By: Relevance
“…Study findings also indicate the importance of assessing early age of first sex as part of routine clinical care, particularly among male adolescents living in a similar social environment, as a marker for intervention and counselling services. The prevalence of first sex at 13 or younger in this clinic-based sample was similar to the recently published rates of early first sex that used metropolitan area studentlevel data of non-Hispanic Black male students in high school (range: 12% to 29%) and middle school (range: 20% to 40%) (Lindberg, Maddow-Zimet, and Marcell 2019). Findings in the current study that showed higher rates of subsequent involvement in a pregnancy contribute to a very small body of literature examining sexual risk outcomes of very early sex onset (O'Donnell, O'Donnell, and Stueve 2001).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Study findings also indicate the importance of assessing early age of first sex as part of routine clinical care, particularly among male adolescents living in a similar social environment, as a marker for intervention and counselling services. The prevalence of first sex at 13 or younger in this clinic-based sample was similar to the recently published rates of early first sex that used metropolitan area studentlevel data of non-Hispanic Black male students in high school (range: 12% to 29%) and middle school (range: 20% to 40%) (Lindberg, Maddow-Zimet, and Marcell 2019). Findings in the current study that showed higher rates of subsequent involvement in a pregnancy contribute to a very small body of literature examining sexual risk outcomes of very early sex onset (O'Donnell, O'Donnell, and Stueve 2001).…”
Section: Discussionsupporting
confidence: 84%
“…brothers, cousins) (Hussen et al 2012) and that these older partners act as "teachers" about sex and influenced how and when sex occurred (Hussen et al 2012;Senn and Carey 2011). Few past studies have examined how consent for sex among male adolescents is obtained and whether sex at very young ages (13 or younger) for males is coercive (Lindberg, Maddow-Zimet, and Marcell 2019). In this study, nearly half of young men reported having mixed feelings about their first sex experience or did not really want it to happen; and one in ten reported being pressured by their partner to have sex, although no significant differences were observed in the proportion of young men reporting decision-making to have sex and sex wantedness by age of first sex at 13 or younger.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the rationale behind the fact that the HPV vaccine is recommended to be given at 11-12 years of age, although it can be administered starting at age 9 (28). In the US, the proportion of males who reported having sexual intercourse before age 13 years varied from 5 to 25% across metropolitan sites (32), hence the need to vaccinate at a young age, designed to capture most teenagers before becoming sexually active. In our study, the onset of sexual activity was not assessed out of concerns that in a multisite trial, the investigators could not assure patient confidentiality relative to their parents/caregivers for all participants.…”
Section: Discussionmentioning
confidence: 99%